The Impact of Social Media on Girl Students Health in Sivagangai District - I. , Sivakumar; K. , Manimekalai; A. , Ranjithkumar (International Journal of Psychosocial Rehabilitation, 2020)
Social media has come up in many different forms, where one is using it for marketing, news, eeducation, jobs search and blogging. Counting on since the year our nation has become independent in 1947 has effusive enhancements in the prospects of media and thereby the status of Indian women in a patriarchal society. It is impacting on lack of knowledge about their basic health in rural areas among women and media not doing any role in giving health literacy or awareness, in urban areas the stereotyping of women and body image distortion shows media has no concern about the health of women altogether. This paper focuses on the condition of the health status of women in India and the role of media to create health-related awareness. The study tries to understand how social media affects girl student’s health. The study found that the women do not even have the knowledge about anemia a simple reason for death which can easily be avoided if they get the knowledge from latest technology. Female infanticide has reached the one crore mark in the last decade in India. A simple random sampling method has been used for this study.